2001
DOI: 10.1007/bf03016692
|View full text |Cite
|
Sign up to set email alerts
|

The addition of fentanyl does not alter the extent of spread of intrathecal isobaric bupivacaine in clinical practice

Abstract: P Pu ur rp po os se e: : Fentanyl is commonly added to intrathecal local anesthetic solutions. In vitro data has shown fentanyl to render isobaric local anesthetics hypobaric, and alter the spread in artificial cerebrospinal fluid. This study examined whether the addition of fentanyl to isobaric bupivacaine with morphine leads to a clinically important alteration in the extent of spread of anesthesia.M Me et th ho od ds s: : Forty-four ASA I III patients undergoing lower limb orthopedic procedures completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
2
11
0
1
Order By: Relevance
“…The opioids (morphine 100 μg, fentanyl 20 μg and sufentanil 5 μg), which are isobaric at room temperature, were hypobaric at 37°C. When combined with LA, the density of the solution fell, making it slightly more hypobaric, although the change was not expected to be clinically significant, consistent with previous reports . Finally, when the hyperbaric LA (8% glucose) was mixed with the same isobaric formulation at equal volumes, the mixture remained hyperbaric in the final state (4% glucose) …”
Section: Mechanisms Governing Spinal Distribution Of Opioidssupporting
confidence: 86%
See 1 more Smart Citation
“…The opioids (morphine 100 μg, fentanyl 20 μg and sufentanil 5 μg), which are isobaric at room temperature, were hypobaric at 37°C. When combined with LA, the density of the solution fell, making it slightly more hypobaric, although the change was not expected to be clinically significant, consistent with previous reports . Finally, when the hyperbaric LA (8% glucose) was mixed with the same isobaric formulation at equal volumes, the mixture remained hyperbaric in the final state (4% glucose) …”
Section: Mechanisms Governing Spinal Distribution Of Opioidssupporting
confidence: 86%
“…When combined with LA, the density of the solution fell, making it slightly more hypobaric, although the change was not expected to be clinically significant, consistent with previous reports. 36,37 Finally, when the hyperbaric LA (8% glucose) was mixed with the same isobaric formulation at equal volumes, the mixture remained hyperbaric in the final state (4% glucose). 10 A recent publication 38 studied the various drug concentrations typically used for intrathecal infusion in chronic pain management, namely bupivacaine (2.5, 5, 10, and 20 mg/mL), morphine (1, 10, 25, and 50 mg/ mL), baclofen (1, 1.5, 2, and 4 mg/mL), and clonidine (0.05, 0.5, 1, and 3 mg/mL), all at 37°C AE 0.01.…”
Section: Intrathecal Transportmentioning
confidence: 99%
“…In this study, neither intrathecal nor intravenous fentanyl affected the block height of spinal anaesthesia. Although the effect of intrathecal fentanyl on the level of sensory block is somewhat controversial, 30–32 Kuusniemi et al 32 reported that the addition of fentanyl produced the same level of sensory analgesia as bupivacaine alone, which was comparable to our results. Moreover, although spinal anaesthesia did not result in significant respiratory depression in all groups, the lowest BIS value caused by spinal anaesthesia was significantly lower in patients with intrathecal fentanyl.…”
Section: Discussionsupporting
confidence: 89%
“…That is, the volume given to patients in Group Ft was slightly larger and more hypobaric. Patterson et al 30 reported previously that the addition of fentanyl does not alter the spread of isobaric bupivacaine in clinical practice and suggested that the effect of baricity on the spread of anaesthesia was negligible. We believe that the difference in the baricity of injectate would have minimal impact on the result of this study.…”
Section: Discussionmentioning
confidence: 97%
“…It has been proposed that positional change after spinal injection plays a major role in promoting cephalad redistribution of hypobaric solution, likely due to cerebrospinal fluid dynamics associated with caval compression and epidural venous engorgement. 17 Distension of the veins of the vertebral plexus causes compression of the dura and results in displacement of cerebrospinal fluid, and any drugs within it, in a cranial direction. However, our study differs from that of Gori et al 16 because plain levobupivacaine was shown to be truly isobaric and therefore its spread is not affected by gravitational forces or positional change.…”
Section: Discussionmentioning
confidence: 99%